2004
DOI: 10.4049/jimmunol.172.12.7703
|View full text |Cite
|
Sign up to set email alerts
|

Stat3 Activation in Acute Lung Injury

Abstract: Stat3 plays diverse roles in biological processes including cell proliferation, survival, apoptosis, and inflammation. Very little is known regarding its activation and function in the lung during acute inflammation. We now show that Stat3 activation was triggered in lungs and in alveolar macrophages after intrapulmonary deposition of IgG immune complexes in rats. Low levels of constitutive Stat3 were observed in normal rat lungs as determined by the EMSA. Stat3 activity in whole lung extracts increased 2 h af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
86
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 96 publications
(90 citation statements)
references
References 50 publications
2
86
0
Order By: Relevance
“…Tissue-specific Stat3 gene deletion mouse models have also defined an important role of Stat3 in tissue injury and wound healing in epithelial cells of the lung and skin (Sano et al, 1999;Gao et al, 2004;Hokuto et al, 2004;Severgnini et al, 2004). In lung epithelial cells, Stat3 is activated in acute lung injury and loss of Stat3 compromises survival following hyperoxia (Gao et al, 2004;Hokuto et al, 2004;Severgnini et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tissue-specific Stat3 gene deletion mouse models have also defined an important role of Stat3 in tissue injury and wound healing in epithelial cells of the lung and skin (Sano et al, 1999;Gao et al, 2004;Hokuto et al, 2004;Severgnini et al, 2004). In lung epithelial cells, Stat3 is activated in acute lung injury and loss of Stat3 compromises survival following hyperoxia (Gao et al, 2004;Hokuto et al, 2004;Severgnini et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to processes involved in tumor formation in epithelial cells, Stat3 plays a crucial role in normal wound healing and response to injury. Stat3 is activated in lung tissues following either lipopolysaccharide (LPS) exposure or intrapulmonary deposition of IgG immune complexes (Gao et al, 2004;Severgnini et al, 2004). Selective Stat3 deletion in lung epithelial cells does not compromise postnatal lung function but mice exposed to hyperoxia develop rapid lung injury characterized by alveolar capillary leak and acute respiratory distress (Hokuto et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Activated Jaks phosphorylate the cytoplasmic domain of the receptor, creating a docking site for Src homology 2-containing proteins such as STAT transcription factors (14). Indeed, our previous work showed that STAT3 is activated in lung during IgG IC-induced acute lung injury, with both Tyr 705 and Ser 727 undergoing phosphorylation (15). Activation of STAT3 in lungs is macrophage and neutrophil dependent.…”
Section: Adenoviral-mediated Overexpression Of Socs3 Enhances Iggmentioning
confidence: 99%
“…Recently, phosphorylation of STAT-1 on serine residue 727 was implicated in STAT-1-mediated effects (41,42). To determine whether serine 727 phosphorylation was induced by IL-10 in monocytic cells, we treated purified monocytes and HL-60 cells with IL-10 for 0 -60 min.…”
Section: Il-10-induced Cd14 Expression Involves the Activation Of Stat-1mentioning
confidence: 99%